2022
DOI: 10.1111/dth.15400
|View full text |Cite
|
Sign up to set email alerts
|

The application of electrolysis of depigmented hair using a trichiasis electrolyzer combined with single hair follicle transplantation for the treatment of vitiligo‐associated leukotrichia

Abstract: Leukotrichia is one of the difficulties of vitiligo treatment. Hair follicle transplantation is an efficient method to treat vitiligo-associated leukotrichia. A trichiasis electrolyzer, commonly used for treating trichiasis, can be used to damage and remove the depigmented hair follicles. To evaluate the efficacy of the electrolysis of depigmented hair using a trichiasis electrolyzer combined with single hair follicle transplantation for the treatment of vitiligo-associated leukotrichia. A total of 15 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recently, minimally invasive transplantation and cosmetic technology of FUT have been developed. Using a trichiasis electrolyzer, depigmented hair follicles could be damaged and removed before transplanting to reduce depigmented hair regeneration ( 56 ). One comparative study on MPG and FUT has found that FUT had a relatively slow process of re-pigmentation, potentially because melanocytes took a long time to migrate from the hair follicle to the epidermis ( 39 ).…”
Section: Surgical Interventionmentioning
confidence: 99%
“…Recently, minimally invasive transplantation and cosmetic technology of FUT have been developed. Using a trichiasis electrolyzer, depigmented hair follicles could be damaged and removed before transplanting to reduce depigmented hair regeneration ( 56 ). One comparative study on MPG and FUT has found that FUT had a relatively slow process of re-pigmentation, potentially because melanocytes took a long time to migrate from the hair follicle to the epidermis ( 39 ).…”
Section: Surgical Interventionmentioning
confidence: 99%
“… 8 A trichiasis electrolyzer, combined with a single hair follicle transplant, was an effective treatment for vitiligo-associated leukotrichia. 9 Some studies have suggested that punch grafting may offer the highest likelihood of repigmentation. 10 It has been also shown that a randomized comparison of excimer laser versus narrow-band ultraviolet B phototherapy after punch grafting in stable vitiligo patients suggests that ultraviolet radiation stimulates melanocyte migration into the vitiliginous skin, increasing repigmentation.…”
Section: Introductionmentioning
confidence: 99%